2020
DOI: 10.9734/arja/2020/v12i430088
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study of Jordanian Consumers’ Attitudes towards Purchasing Organic Food

Abstract: The study aimed to determine the level of consumer attitudes towards purchasing organic food, by conducting a statistical analysis of the data collected from the questionnaires collected from a sample of consumers in Amman Governorate in 2018 distributed to a sample of 384. The analytical descriptive approach was used in this research to study the relationship Between the variables, the results of the study showed that the average degree of consumers to purchase organic foods was 3.69 degrees, which is a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The result was parallel with the study conducted in India by Kumar and Ali (2011), who found that educated people and people with high monthly income were more aware towards organic products. Altarawneh (2013) in his study in Jordon also revealed that increase in education and increase in income level, increased the awareness towards organic product. Higher number of economically active female increased likelihood of awareness towards organic product by 2.396 factors but increase in economically active male member decreased likelihood of awareness towards organic product by 0.315 factors.…”
Section: Figure 2 Awareness Of Organic Products In Studied Areamentioning
confidence: 92%
“…The result was parallel with the study conducted in India by Kumar and Ali (2011), who found that educated people and people with high monthly income were more aware towards organic products. Altarawneh (2013) in his study in Jordon also revealed that increase in education and increase in income level, increased the awareness towards organic product. Higher number of economically active female increased likelihood of awareness towards organic product by 2.396 factors but increase in economically active male member decreased likelihood of awareness towards organic product by 0.315 factors.…”
Section: Figure 2 Awareness Of Organic Products In Studied Areamentioning
confidence: 92%
“…The FROM and PROM 1RM DL scores were compared with a pair t test, and Cohen's (3) effect size (ES) was calculated. Statistical calculations were conducted with Microsoft Excel 2013, and data were peer reviewed as suggested by AlTarawneh et al (1).…”
Section: Methodsmentioning
confidence: 99%